BUILDING BRIDGES: IMPROVING BEGINNING TEACHERS’ CULTURALLY RELEVANT TEACHING PRACTICES - Matkins, Jerry Taylor, Jr (East Carolina University, 2021)
Schools across the United States are becoming more diverse and the way they respond to that diversity could make all the difference in the success of future generations. The purpose of this participatory action research study was to provide beginning teachers with a better understanding of how culture plays a role in teaching and learning. This study included a community of beginning teachers over one calendar year. During that year, the beginning teachers took part in several Community Learning Exchanges (CLEs) that created mutual trust and understanding of cultures. The findings of this project support the conclusion that when teachers successfully implement culturally relevant teaching (CRT) strategies, they create common ground, understand cultural influences, and understand the importance of relationships. When CRT strategies are incorporated, an equitable learning environment is created. The policy, practice, and research implications for educational leaders can lead to beginning teachers that understand their students better.
Keywords: relationships; Culturally relevant pedagogy--United States; Educational equalization--United States; Classroom environment--United States